Typology of the Influence of Qirāʾāt Variations on the Interpretation and Istinbāṭ of Islamic Law: Linguistic and Juridical Analysis of Aḥkām Verses - Saifullah (Ushuluddin, Adab, and Dakwah Faculty of State Islamic University Ponorogo, 2026)
Studies of qirāʾāt (variant Qur’anic readings) typically focus on the authenticity of oral transmission, which often results in a fragmented examination of their impact on the development of Islamic law. To address this, the current study develops a comprehensive analytical framework that classifies how variations in qirāʾāt influence exegesis (Qur’anic interpretation) and legal deduction (istinbāṭ) in legal verses (ayāt aḥkām). Employing a library research method with an integrative approach, the study encompasses Arabic linguistics—morphology (ṣarf), syntax (naḥw), semantics (dalālah), phonology (ṣawt)—as well as legal methodology (usul al-fiqh). The data is analyzed comprehensively and typologically through the integration of the theory of resolving conflicts of evidence (taʿāruḍ al-adillah). The findings identify four systematic typological models for the influence of recitation variations on legal construction: (1) the Cumulative-Complementary typology, which unites complementary dimensions of meaning without altering the substance of the law; (2) the Conditional-Qualitative typology, which sets strict conditions for legal implementation via changes in verb patterns; (3) the Differentiative-Alternative typology, where shifts in iʿrāb (grammatical case) diacritics polarize schools of thought yet offer alternative legal pathways; and (4) the Categorical-Conceptual typology, which underlies debates in ushūl al-fiqh concerning the boundaries of literal and figurative meaning. Epistemologically, these findings confirm that the plurality of Islamic law (ikhtilāf al-fuqahāʾ) has a valid textual-linguistic foundation inherent in the very structure of revelation. This foundational plurality reflects the flexibility of sharia (Islamic law).